Immunotherapy as an alternative therapy for myasthenia gravis - Meyvita Silviana; Endang Kustiowati (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2025)
Myasthenia gravis is an autoimmune disorder characterised by fluctuating, progressive weakness of skeletal muscles and activity-related fatigability. It most commonly affects young women and older men. The disease results from dysfunction at the neuromuscular junction involving acetylcholine signalling and calcium ions. Autoantibodies directed against the nicotinic acetylcholine receptor (AChR) are the principal cause of muscle weakness in many patients with myasthenia gravis. Frequently affected muscles include those controlling eye movements and eyelid elevation, chewing, swallowing, coughing, and facial expression; proximal limb and neck muscles, as well as respiratory muscles, may also be involved. Clinically, patients experience variable skeletal muscle weakness that worsens with exertion and improves with rest. Typical initial symptoms include diplopia, ptosis, dysphagia with recurrent aspiration, and difficulty chewing. Diagnostic investigations commonly used to establish the diagnosis include assays for anti-acetylcholine receptor antibodies and imaging such as chest radiography and MRI. Standard treatments comprise acetylcholinesterase inhibitors, corticosteroids, other immunosuppressive agents, and thymectomy. This review focuses on the pathophysiology of myasthenia gravis and current management strategies, with particular emphasis on immunotherapies that target components of the immune system.